TRADISI KALANGKAh DALAM PERKAWINAN ADAT SUNDA PERSPEKTIF ‘URF: in Desa Pananjung , Kecamatan Pangandaran , Kabupaten Pangandaran - Fuaji, Yasir (LPPM UNHASY, 2025)
This study investigates the persistence and social significance of the Kalangkah tradition in Sundanese customary marriages in Pananjung Village, Pangandaran District, Indonesia. The Kalangkah tradition refers to a prohibition against younger siblings marrying before their older brothers or sisters, a practice deeply rooted in local belief and cultural norms. While some community members perceive dire consequences—such as disharmonious households or difficulty finding a marital partner—for violating this tradition, others regard it merely as ancestral advice or myth with no tangible effects. Employing a qualitative field research design with a sociological approach, the study collects data through observation, interviews, and documentation. The findings reveal that, although the Kalangkah tradition continues to shape marriage practices and beliefs among villagers, its practical impact is subjective and varies among individuals. Community leaders emphasize that such customs should be interpreted flexibly, recognizing divine will (Qada and Qadar of Allah SWT) as the ultimate determinant in life events. From the perspective of Islamic law, the prohibition embedded in local custom does not pose a religious issue as long as it does not contradict the principles of sharia or state regulations. In line with the theory of 'Urf (customary law), the study concludes that cultural traditions like Kalangkah can coexist with Islamic norms and be preserved without legal or religious conflict